NT5C2 germline variants alter thiopurine metabolism and are associated with acquired NT5C2 relapse mutations in childhood acute lymphoblastic leukaemia. Issue 12 (December 2018) - Tulstrup, Morten; Grosjean, Marie; Nielsen, Stine; Grell, Kathrine; Wolthers, Benjamin; Wegener, Peder; Jonsson, Olafur; Lund, Bendik; Harila-Saari, Arja; Abrahamsson, Jonas; Vaitkeviciene, Goda; Pruunsild, Kaie; et al.
Abstract The antileukaemic drug 6-mercaptopurine is converted into thioguanine nucleotides (TGN) and incorporated into DNA (DNA-TG), the active end metabolite. In a series of genome-wide association studies, we analysed time-weighted means (wm ) of erythrocyte concentrations of TGN (Ery-TGN) and DNA-TG in 1009 patients undergoing maintenance therapy for acute lymphoblastic leukaemia (ALL). In discovery analyses (454 patients), the propensity for DNA-TG incorporation (wm DNA-TG/wm Ery-TGN ratio) was significantly associated with three intronic SNPs inNT5C2 (top hit: rs72846714;P = 2.09 × 10−10, minor allele frequency 15%). In validation analyses (555 patients), this association remained significant during both early and late maintenance therapy (P = 8.4 × 10−6 and 1.3 × 10−3, respectively). The association was mostly driven by differences inwm Ery-TGN, but in regression analyses adjusted forwm Ery-TGN (P < 0.0001), rs72846714-A genotype was also associated with a higherwm DNA-TG (P = 0.029). Targeted sequencing ofNT5C2 did not identify any missense variants associated with rs72846714 orwm Ery-TGN/wm DNA-TG. rs72846714 was not associated with relapse risk, but in a separate cohort of 180 children with relapsed ALL, rs72846714-A genotype was associated with increased occurrence of relapse-specificNT5C2 gain-of-function mutations that reduce cytosol TGN levels (P = 0.03). These observations highlight the impact of both germline and acquired mutations in drug metabolism and disease trajectory.